Design and development of Image processing algorithms for quantitative road traffic data analysis - Nair, Pranav Mohandas (2014)
The project aims to design and develop efficient algorithms using image processing techniques for the quantitative analysis of road traffic data in addition to enabling a better learning experience of a more commonly used software MATLAB. Road traffic data has been a major concern for traffic engineers in optimizing the efficiency and capacity of any modern transport system. The project aspires to develop a real time traffic analysis system for monitoring traffic flow, collect statistical data of traffic analysis and enhance the alogrithms in place to attain higher efficiency.